Dinuclear Silver(I)-N- Heterocyclic Carbene Complexes Based On Imidazolium Derivatives: Synthesis And Biological Activities - Selvarajoo,, Puvana Devi (2018)
This research describes the syntheses of two new series, non-functionalized series of four new precursor salts , namely 3,3' [(1,2 phenylenebis(methylene)] bis(1-cyclopentylimidazolium bis-hexaflourophosphate (1), 3,3' [(1,3 phenylenebis(methylene)] bis(1-cyclopentylimidazolium) bis-hexaflourophosphate (2), 3,3' [(1,4 phenylenebis(methylene)] bis(1-cyclopentylimidazolium) bis-hexaflourophosphate (3), 3,3' [(ethane-1,2-diyl)] bis(1-cyclopentylimidazolium) bis-hexaflourophosphate (4) and nitrile functionalized series of four new correspondence salt, namely 3,3' [(1,2 phenylenebis(methylene)] bis(4'-benzonitrilelimidazolium) bis-hexaflourophosphate (9), 3,3' [(1,3 phenylenebis(methylene)] bis(4'-benzonitrilelimidazolium) bis-hexaflourophosphate (10), 3,3' [(1,4 .